What Can the Blood Tell us About Food and Health? - Noerman Stefania; Kolehmainen Marjukka; Hanhineva Kati (Frontiers Research Foundation, 2025)
When we eat, foods are broken down into smaller parts by the body. These smaller parts are called metabolites. Depending on the foods we eat, different metabolites enter the body. Microbes living in the gut can also take part in making metabolites. Metabolites from food or microbes can both appear in the blood. Studying blood metabolites could tell us what kinds of foods people generally eat or how healthy they are. To find out how eating different foods changes blood metabolites, we collected results from many previous experiments. We found that studying blood metabolites can tell us how food affects people’s bodies. Interestingly, we also found that these effects appear to be different for each person.